Austempering and Cryogenic treatment of Vanadium modified Carbidic Ductile Iron - Kumar S.; Ghose A.K.; Chakrabarty I. (My University, 2025)
Conventional Austempered Ductile Irons (ADI) are lacking in adequate wear resistance. Introduction of hard alloy carbide phase in the microstructure by strong carbide formers imparts wear resistance. Deep cryogenic treatment subsequent to austempering is another way to improve the wear resistance without a major reduction in toughness. The present study encompasses the microstructural evolution following deep cryogenic treatment and the resultant bulk hardness, Charpy impact toughness and dry sliding wear of two vanadium contained (0.1% and 0.3%) carbidic austempered ductile irons. The irons were austempered at two temperatures viz. 3000 C and 3500 C for 30, 45, and 60 minutes and which is accompanied at −1960 C either by deep cryogenic treatment or air-cooled. EDS & XRD (X-ray Diffraction), Optical and Scanning Electron Microscopy analysis have characterized the microstructural features. Increase in vanadium content and cryo-treatment result in a prominent combination of wear resistance and impact toughness. © 2021 Taylor & Francis.